Autoimmune regulator and self‐tolerance – molecular and clinical aspects. Issue 1 (May 2016) - Abramson, Jakub; Husebye, Eystein S.
Summary: The establishment of central tolerance in the thymus is critical for avoiding deleterious autoimmune diseases. Autoimmune regulator (AIRE), the causative gene in autoimmune polyendocrine syndrome type‐1 (APS‐1), is crucial for the establishment of self‐tolerance in the thymus by promoting promiscuous expression of a wide array of tissue‐restricted self‐antigens. This step is critical for elimination of high‐affinity self‐reactive T cells from the immunological repertoire, and for the induction of a specific subset of Foxp3 + T‐regulatory (Treg ) cells. In this review, we discuss the most recent advances in our understanding of how AIRE operates on molecular and cellular levels, as well as of how its loss of function results in breakdown of self‐tolerance mechanisms characterized by a broad and heterogeneous repertoire of autoimmune phenotypes.